Deep generative models: third MICCAI workshop, DGM4MICCAI 2023 : held in conjunction with MICCAI 2023, Vancouver, BC, Canada, October 8, 2023 : proceedings - Mukhopadhyay, Anirban; Oksuz, Ilkay; Engelhardt, Sandy; Zhu, Dajiang; Yuan, Yixuan (Lecture notes in computer science, 2024)
This LNCS conference volume constitutes the proceedings of the third MICCAI Workshop, DGM4MICCAI 2023, Held in Conjunction with MICCAI 2023, Vancouver, BC, Canada, October 2023. The 23 full papers included in this volume were carefully reviewed and selected from 38 submissions. The conference presents topics ranging from methodology, causal inference, latent interpretation, generative factor analysis to applications such as mammography, vessel imaging, and surgical Videos